Investigation of metabolites associated with confinement odour in chilled vacuum-packed lamb by proton nuclear magnetic resonance (1H NMR) spectroscopy. (November 2020) - Cônsolo, Nara R.B.; Olivecrona, Natalia; Samuelsson, Linda M.; Reis, Mariza G.; Edwards, Patrick J.B.; Reis, Marlon M.
Abstract: This study aimed to determine the profiles of water-soluble metabolites in lamb drip and meat by Nuclear Magnetic Resonance (NMR) spectroscopy, in order to better understand the confinement odour (CO) phenomenon in lamb meat on a molecular level. Thirty-five lamb legs were obtained from two New Zealand meat processing plants and stored for 11 to 13 weeks at temperatures ranging from −1.5 °C to +4.0 °C. A sensorial test classified meat samples as having CO, no odour (NO) or persistent odour (PO). Sixty-three and sixty-two metabolites were identified and quantified in drip and meat samples, respectively. Partial least squares canonical analysis (PLS-CA) showed that CO was correlated with meat and drip metabolites tyramine, formate, alanine, carnosine, urea, proline, aspartate, glutathione and nicotinate. CO was also positively associated with appearance and bloom, but not directly associated with pH, size of the bacterial population or with processing plant. Metabolites associated with CO/PO are substrates or products of glucose fermentation and amino acid catabolism.